Evaluation of Growth Performance of Kuchi Indigenous Chicken Ecotype Fed with Three Levels of Energy Diets in Three Different Systems of Management - B. K. , Chesoo; G. W. , Oduho; D. K , Kios; J. K , Kitilit; H. A , Rachuonyo (African Journal of Education,Science and Technology (AJEST), 2015)
A study was conducted to evaluate the growth performance of Kuchi indigenous chicken (IC) ecotype of Kenya. This ecotype has become popular for its high mature body weight. From week 12 to17, growth performance of the Kuchi growers was evaluated on the effects of three levels of energy diets: High (HE) 2700.5 MEKcal/Kg, Low (LE) 2564 MEKcal/kg and milled Maize Grain (MG); all managed under three systems of management: Extensive (ES),Extensive with Supplementation(ESS) and Intensive(IS). The HE and LE rations were specifically formulated for the experiments which were fed to the Kuchi growers on a two week change-over basis from week up to week 17.The experiment was laid under a Randomized Completely Block Design(RCBD);with three treatments(energy diet),three Blocks with two replicates(period in weeks)each with six experimental animals. Mean weekly weights were computed and analyzed by ANOVA using SAS (2011) software tool. Both Fisher‘s LSD and Duncan Student‘s Range were applied in separating means where differences were observed. Differences among management systems were not (p>0.05) statistically significant. Diet LE 2564MEKcal/kg had significant effect (p<0.05) on Kuchi growers; While diets HE and MG had no significance (p>0.05). It is concluded that Kuchi does not need an intensified management. Furthermore, a grower‘s supplementation ration of about 2564.5MEKcal/Kg is optimal under an extensive production system.